Value-Oriented Consciousness - V. V. Matyushina (Vestnik MGIMO-Universiteta)
The article regards the interrelation between language and consciousness, but with a special focus on the fact that consciousness is not only the tool and method of reflecting human existence or regulating human actions and relations, but it is as well a special device of evaluating the items and phenomena of real life. Consciousness is understood as a person's world outlook. Society members create and get knowledge in the course of cognitive coactivity. Speech is considered to be one of the types of activity. Outwardly the images of consciousness that are figured in the course of activity are expressed with the help of language tools. The procedure of studying consciousness in psychology is described, in psychology consciousness is understood as a person's image of the world, the connection between consciousness (or the image of the world) and the category of linguistic consciousness is traced, linguistic consciousness is thought to be an integral part of consciousness. As in psychology consciousness is compared with and likened to the so called image of the world, the latter can be represented in a form of the system of meanings. The system of meanings that is moulded in the course of perceiving the real world services and works as a specific system to direct a person in life. The knowledge gained in the course of activity is transformed into personal experience and expertise in a person's consciousness. The essence of the fundamental paradigm of modern psycholinguistics is revealed where the image of linguistic consciousness is the basic research pattern. The image of linguistic consciousness is determined as the image of the world mediated by language, or it can be presented as a collection of images of consciousness expressed with the help of language tools. The images of consciousness exist as word meanings. An attempt is made to prove that linguistic consciousness not only forms, stores or processes language signs and their meanings but also determines the attitude of a person to the items and phenomena of real life. Linguistic consciousness where the axiological factor is regarded as its essence directs a person's activity, determines a person's attitude to the items and phenomena of real life. On the basis of all above - mentioned it is proved that the element of value does exist in linguistic consciousness. Consequently values can be defined as the words with socially built meaning.